Perlindungan Konsumen Terhadap Klausula Eksonerasi Dalam Perjanjian Baku Perusahaan Jasa Pengiriman Barang (Studi Pada Perusahaan Pengiriman Barang Di Kota Binjai PT. JNE) - Dara Qurratu Aini Yusuf (Iuris Studia: Jurnal Kajian Hukum, 2022)
Standard agreements using exoneration clauses have begun to develop in the community and are used for reasons of saving costs and time. However, the frequent use of exoneration clauses in standard agreements can lead to many things that do not meet the requirements so that there are parties who gain losses and there are also parties who benefit or get more protection from the contents of the agreement. The discussion of the problem in this thesis is how the effect of the exoneration clause in the standard agreement stipulated at the freight forwarding company (PT. JNE), how the settlement of compensation by PT. JNE against losses suffered by the sender due to the use of standard agreements, how consumer protection against the standard agreement exoneration clause is studied based on Law Number 8 of 1999 concerning Consumer Protection. The research in this thesis was carried out by using normative and empirical law research methods. Normative juridical research is research that discusses legal doctrines or principles that aim to find applicable positive legal principles. Empirical juridical research is research that refers directly to the situation in the field. Legal materials related to this thesis were obtained through interviews with PT. JNE and consumers. Based on the research conducted, the results of this thesis are that in Law Number 8 concerning Consumer Protection Article 18 explains the prohibition on making and or including an exoneration clause in every document or agreement. The existence of an exoneration clause in a standard agreement made by a freight forwarder causes the principle of balance to not be created because the position of the consumer does not get the right to change the contents of the agreement. This agreement gives many advantages to the freight forwarder, but the shipper is still willing to sign a standard agreement on the grounds of need or need for services from the company. The contents of the standard agreement tend to violate Article 1320 of the Civil Code. The validity of an agreement begins with the agreement of the parties who make an agreement and the agreement agreement is based on the principle of balance which in this principle requires both parties to carry out the agreement.